2005
DOI: 10.1093/brain/awh658
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular nodular heterotopia with overlying polymicrogyria

Abstract: Polymicrogyria (PMG) and periventricular nodular heterotopia (PNH) are two developmental brain malformations that have been described independently in multiple syndromes. Clinically, they present with epilepsy and developmental handicaps in both children and adults. Here we describe their occurrence together as the two major findings in a group of at least three cortical malformation syndromes. We identified 30 patients as having both PNH and PMG on brain imaging, reviewed clinical data and brain imaging studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 41 publications
3
49
0
4
Order By: Relevance
“…Several particular patterns of polymicrogyria have been described; the main one is bilateral perisylvian polymicrogyria, clinically characterized by a combination of pseudobulbar palsy, spastic tetraparesis, learning difficulties and epilepsy. Some specific combinations of periventricular nodular heterotopia with overlying polymicrogyria have also been described 3,46,48,49 . Moreover, the fact that there is necrotic tissue within the malformed cortex, that most changes occur in the middle cerebral artery territory, and the existence of polymicrogyria adjacent to the borders of schizencephaly and porencephaly, suggest that hypoxic-ischemic insults may, at least in some cases, be related to the genesis of polymicrogyria 5 .…”
Section: Polymicrogyriamentioning
confidence: 99%
“…Several particular patterns of polymicrogyria have been described; the main one is bilateral perisylvian polymicrogyria, clinically characterized by a combination of pseudobulbar palsy, spastic tetraparesis, learning difficulties and epilepsy. Some specific combinations of periventricular nodular heterotopia with overlying polymicrogyria have also been described 3,46,48,49 . Moreover, the fact that there is necrotic tissue within the malformed cortex, that most changes occur in the middle cerebral artery territory, and the existence of polymicrogyria adjacent to the borders of schizencephaly and porencephaly, suggest that hypoxic-ischemic insults may, at least in some cases, be related to the genesis of polymicrogyria 5 .…”
Section: Polymicrogyriamentioning
confidence: 99%
“…MALFORMATIONS DUE TO ABNORMAL NEURONAL MIGRATION

A. MALFORMATIONS WITH NEUROEPENDYMAL ABNORMALITIES: PERIVENTRICULAR HETEROTOPIA Anterior predominate and diffuse PNH       Clinically defined with unknown cause Diffuse PNH with/without sparing of temporal hornsDiffuse PNH composed of micronodulesDiffuse PNH with frontonasal dysplasia (Guerrini and Dobyns, 1998)Anterior predominant PNHAnterior predominant PNH with fronto-perisylvian PMG (Wieck et al ., 2005)Unilateral or bilateral isolated PNH       Genetically defined with AD inheritance (new mutations)Anterior PNH with duplication 5p15.1 (Sheen et al ., 2003)Anterior or diffuse PNH with duplication 5p15.33 (Sheen et al ., 2003)Diffuse (but variable) PNH with del 6q27 (W.B.D, in preparation)PNH and Williams syndrome with del 7q11.23, including HIP1 and YWHAG (Ferland et al ., 2006; Ramocki et al ., 2010)PNH with del 4p15 (gene not identified) (Gawlik-Kuklinska et al ., 2008)PNH with deletion 5q14.3–q15 (Cardoso et al ., 2009)PNH and agenesis of the corpus callosum with del 1p36.22-pter (Neal et al ., 2006)       Genetically defined with XL inheritanceBilateral PNH due to mutations of FLNA , with/without Ehlers–Danlos (Sheen et al ., 2001; Parrini et al ., 2006)PNH and Fragile X syndrome (Moro et al ., 2006)Posterior predominant (temporal-trigonal) PNH       Clinically defined with unknown cause Posterior PNH onlyPosterior PNH with hippocampal dysgenesis, colpocephaly, anomalies of midbrain tectum or cerebellar hypoplasiaPosterior PNH with posterior PMG (Wieck et al ., 2005)Periventricular heterotopia, not nodular (unilateral or bilateral)       Clinically defined with unknown cause Diffuse PLHFrontal predominant PLHPosterior predominant PLHRibbon-like heterotopia, bilateral undulating heterotopic band       Clinically defined with unknown cause Posterior predominant ribbon-like heterotopiaDiffuse ribbon-like heterotopia

B. MALFORMATIONS DUE TO GENERALIZED ABNORMAL TRANSMANTLE MIGRATION (radial and non-radial)

Anterior predominant or diffuse classic (four-layered) LIS and SBH

       Clinically defined with unknown cause

Anterior predominant LIS with abrupt transition and cerebellar hypoplasia (previously LCHe)

Anterior predominant or diffuse LIS (ILS)

       Clinically defined with AR inheritance

Anterior predominant LIS (ILS) with AR inheritance

Winter–Tsukahara syndrome (Levin et al ., 1993)

       Clinically defined with AD (new mutation) inheritance

Baraitser–Winter syndrome with anterior or diffuse LIS–SBH (Rossi et al ., 2003)

Anterior predominant LIS (ILS) or SBH with DCX mutation at Xq22.3–q23 (Dobyns et al ., 1999)

…”
Section: Appendixmentioning
confidence: 99%
“…Clinically defined with unknown cause Diffuse PNH with/without sparing of temporal hornsDiffuse PNH composed of micronodulesDiffuse PNH with frontonasal dysplasia (Guerrini and Dobyns, 1998)Anterior predominant PNHAnterior predominant PNH with fronto-perisylvian PMG (Wieck et al ., 2005)Unilateral or bilateral isolated PNH       Genetically defined with AD inheritance (new mutations)Anterior PNH with duplication 5p15.1 (Sheen et al ., 2003)Anterior or diffuse PNH with duplication 5p15.33 (Sheen et al ., 2003)Diffuse (but variable) PNH with del 6q27 (W.B.D, in preparation)PNH and Williams syndrome with del 7q11.23, including HIP1 and YWHAG (Ferland et al ., 2006; Ramocki et al ., 2010)PNH with del 4p15 (gene not identified) (Gawlik-Kuklinska et al ., 2008)PNH with deletion 5q14.3–q15 (Cardoso et al ., 2009)PNH and agenesis of the corpus callosum with del 1p36.22-pter (Neal et al ., 2006)       Genetically defined with XL inheritanceBilateral PNH due to mutations of FLNA , with/without Ehlers–Danlos (Sheen et al ., 2001; Parrini et al ., 2006)PNH and Fragile X syndrome (Moro et al ., 2006)…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Patients in this study had more severe cerebellar dysgenesis than that observed in patients with classic bilateral PNH due to FLNA mutations. 4 The reason why cerebellar dysgenesis, often severe, is associated with posteriorly predominant PNH and under-rotated hippocampi, sometimes merging with the heterotopia, remains cryptic. In both mouse models and humans, regionspecific transcription factor genes have been characterized that are primarily expressed in both the cerebellum and archicortex, such as Neurod2 18 and OTX2.…”
Section: Discussionmentioning
confidence: 99%